2017
DOI: 10.1053/j.gastro.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum Increases Proliferation of Colorectal Cancer Cells and Tumor Development in Mice by Activating Toll-Like Receptor 4 Signaling to Nuclear Factor−κB, and Up-regulating Expression of MicroRNA-21

Abstract: Background & Aims Nearly 20% of the global cancer burden can be linked to infectious agents. Fusobacterium nucleatum promotes tumor formation by epithelial cells via unclear mechanisms. We aimed to identify microRNAs (miRNAs) induced by F nucleatum and evaluate their ability to promote colorectal carcinogenesis in mice. Methods Colorectal cancer (CRC) cell lines were incubated with F nucleatum or control reagents and analyzed in proliferation and would healing assays. HCT116, HT29, LoVo, and SW480 CRC cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
686
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 736 publications
(714 citation statements)
references
References 47 publications
19
686
2
7
Order By: Relevance
“…Fusobacterium nucleatum numbers are significantly correlated with tumor size, and shortened survival times in a population of human Japanese patients with later stage CRC compared to earlier stages 53. These findings, as well as additional observations in rodent models and humans with CRC suggest that chronic inflammatory disease of the GI tract is a potential risk factor for the development of additional channels for amplified inflammatory processes, aneuploidy, high‐grade dysplasia, metaplasia and loss of cellular proliferative checkpoints, all of which are processes that can be appreciated in malignancy 13, 19, 54, 58, 59. The increased numbers of mucosal Fusobacterium spp.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Fusobacterium nucleatum numbers are significantly correlated with tumor size, and shortened survival times in a population of human Japanese patients with later stage CRC compared to earlier stages 53. These findings, as well as additional observations in rodent models and humans with CRC suggest that chronic inflammatory disease of the GI tract is a potential risk factor for the development of additional channels for amplified inflammatory processes, aneuploidy, high‐grade dysplasia, metaplasia and loss of cellular proliferative checkpoints, all of which are processes that can be appreciated in malignancy 13, 19, 54, 58, 59. The increased numbers of mucosal Fusobacterium spp.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, CD11b + myeloid cells might contribute to development of a tumor microenvironment,19, 63 and Fusobacterium spp. might induce toll like receptors (TLR), to stimulate NF‐κB through the TLR4/MYD88 pathway 54. Importantly, TLRs are found on both immune and non‐immune cells, and can be expressed on tumors including human mantle cell lymphoma 21, 64…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to Kostic’s results, introduction of Fn increased the number of tumors in C57BL/6 Apc Min/+ mice (18). Similarly, Yang et al showed that introduction of Fn into C57BL/6 Apc Min/+ mice increased the number and size of tumors, and shortened overall survival compared with the non-treated controls (19). Although these three studies suggest that Fn infection may promote loss of a wild-type copy of Apc in Apc Min/+ colon cells to form adenoma, they do not give evidence that Fn infection may be involved in adenoma-to-carcinoma transition in the colon and rectum.…”
Section: Mouse Model Of Fn-associated Intestinal Tumorigenesismentioning
confidence: 96%
“…Increased loads of Fn are associated with advanced CRC stages (6,1618) and with poor prognoses (19,4346). Mima et al showed that colon cancer-specific death, but not overall survival is associated with high levels of tissue Fn (43).…”
Section: Characteristics Of Fusobacterium-associated Crcsmentioning
confidence: 99%